Tilling capacity as an element of Sudan grass productivity - N. A. Kovtunova; V. V. Kovtunov; E. A. Shishova; A. E. Romanyukin (Аграрная наука Евро-Северо-Востока)
The physiological bases for Sudan grass tilling capacity and methods for its regulation have not been sufficiently  studied, since this trait is affected by both a genotype and the environment. The purpose of the research was to identify the dependence of tilling capacity of Sudan grass cultivars on external growing conditions (weather factors, sowing methods), to determine the effect of the trait on productivity, green mass quality of the crop. The study was carried out in the Rostov region in 2018–2024 using generally accepted methods. The objects of the study were 4 Sudan grass cultivars developed by the FSBSI “Agricultural Research Center “Donskoy” and 8 samples as the sources of high tilling capacity. Weather conditions during the “seedlings - heading” period varied from very severe drought in 2024 (HTC – 0.29) to insufficient moisture in 2020, 2021 and 2023 (HTC – 0.90 ... 1.02). With wide-row sowing (70 cm between rows), the tilling capacity was higher on average among the cultivars with 2.2 stems per plant, than that with row sowing (15 cm) with 1.7 stems per plant. There has been found that Sudan grass tilling capacity correlates with the sum of active temperatures for both wide-row (r = 0.26±0.19) and row sowing (r = 0.39±0.18). The tilling capacity of plants with wide-row sowing also depends on precipitation (r = 0.40±0.18) and affects green mass productivity (r = 0.28±0.16). There has been no correlation with seed productivity. There has been established a mean positive correlation between tilling capacity and protein percentage in green mass both with wide-row (r = 0.52±0.16) and row (r = 0.65±0.15) sowing methods. There was 12.9–14.3 % of crude protein in green mass of the identified sources of high tilling capacity with 5.0...8.5 stems per plant, such as ‘K-447’, ‘K-384’, ‘Priobskaya 97’, ‘Mechta Povolzhiya’, ‘Penzenskaya rannyaya’, ‘K-335’, ‘Golubovskaya’, ‘Voronezhskaya’, when the standard cultivar ‘Alexandrina’ was characterized with 2.4 stems per plant and 10.4 % of crude protein.